

Đinh Thị Kim Ngân
Giới thiệu về bản thân
Chào mừng bạn đến với trang cá nhân của Đinh Thị Kim Ngân





0





0





0





0





0





0





0
2025-03-15 22:52:30
a) xy + y² - x - y
= x ( y - 1 ) + y ( y - 1 )
= ( y- 1 ) ( x + y )
b) ( x²y² - 8 )² - 1
= ( x²y² - 8 - 1 ) ( x²y² - 8 + 1 )
= ( x²y² - 9 ) ( x²y² - 7 )
2025-03-15 22:42:50
a) ( - 12x¹³y¹⁵ + 6x¹⁰y¹⁴ ) : ( - 3x¹⁰y¹⁴ )
= -12x¹³y¹⁵ : ( - 3x¹⁰y¹⁴ ) + 6x¹⁰y¹⁴ : ( - 3x¹⁰y¹⁴ )
= 4x³y - 2
b) ( x- y ) ( x² - 2x + y ) - x³ + x²y
= x³ - 2x² + xy - x²y + 2xy - y² - x³ + x²y
= 2x² + 3xy - y²